Teachers’ Perception of Classroom Lesson Hour in Secondary Schools in Ilorin South Local Government, Kwara State - OYENIRAN, Saheed; AKINLOWO, Shakirat Abimbola (Ilorin Journal of Education, 2024)
This study investigated the perceptions of teachers on classroom lesson hours in secondary schools in Kwara State. The research design employed was a survey type of descriptive research using an instrument titled "Perceptions of Teachers on Classroom Lesson Hour Questionnaire" (PTCLHQ). Validity of the instrument was carried out by experts in the area of Test and Measurement and Educational Management. The reliability coefficient of the PTCLHQ was (r=0.78). The population consisted of 1,178 teachers across 21 public senior secondary schools in Ilorin South Local Government Area, Kwara state, with a sample size of 300 teachers selected using a simple random sampling technique. The collected data were analyzed using descriptive statistics. The findings revealed that the stipulated time for instructional activities in secondary schools in Kwara State is insufficient. However, the lesson objectives were attainable within the stipulated lesson hour. Teachers opined that the school lesson duration should be increased to effectively achieve the lesson objectives. The most prominent factor affecting classroom lesson hours was identified as student indiscipline, while teachers' low self-efficacy to teach was considered the least influential factor. Based on the findings, it was recommended that education authorities should conduct a comprehensive review of classroom lesson hours to align them with the needs of teachers and students. Additionally, professional development programs for teachers should focus on enhancing teachers' instructional strategies and time management skills.